PENGEMBANGAN BUKU CERITA MATEMATIKA PADA KELAS VII SMP DALAM MATERI PERBANDINGAN - Desi, D.; Lumbantoruan, J. H. (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
This study aims to determine the feasibility of developing an mathematics story book. The method used in this study is "Research and Development". Meanwhile, the data collection technique in this study was a validator questionnaire from the experts, then quantitative and qualitative data were analyzed descriptively.Based on the results of research and development that has been done, it shows that: mathematics story books get a very decent percentage value. This percentage is obtained from the results of the validation of each expert i.e. Material experts with a percentage of 80.92%, experts in presenting material with a percentage of 79.16%, media experts giving a score of 93.75%, and linguists giving a score of 81.25%. So it can be concluded that the average value of the percentage of experts is in the very feasible category with a percentage value of 83.77%. Based on the explanation above, it can be concluded that the electronic mathematics storybook is very suitable to be used as a learning tool in class VII SMP in comparison material. Keywords: development, mathematics storybook, comparison.